Racial Disparities in the Content of Primary Care Office Visits - Franks, Peter (Blackwell Science Inc, 2005)
BACKGROUND: Little is known about racial disparities in primary care at the level of the office visit. OBJECTIVE: To assess racial disparities in the receipt of commonly performed/recommended procedures during routine primary care office visits and examine trends in disparities over time. DESIGN, SETTING, AND PATIENTS: The sample included 88,303 visits by adults to 3,260 primary care physicians in office-based practices in the National Ambulatory Medical Care Surveys, 1985, 1989, 1990, 1991, 1992, and 1995 to 2001. MEASUREMENTS: Adjusted odds for receipt or recommendation of commonly performed office procedures. RESULTS: During the years 1985 to 2001, African Americans, compared with whites, had lower odds of receiving a Pap test (odds ratio (OR) 0.81; 95% confidence interval (CI) 0.70 to 0.93), rectal exam (OR 0.67; 95% CI 0.56 to 0.80), smoking cessation counseling (OR 0.80; 95% CI 0.66 to 0.96), and mental health advice (OR 0.51; 95% CI 0.38 to 0.69), but had higher odds for visual screening (OR 1.38; 95% CI 1.08 to 1.77), weight advice counseling (OR 1.27; 95% CI 1.13 to 1.44) and receiving a follow-up appointment (OR 1.45; 95% CI 1.29 to 1.64). These findings were not appreciably altered by adjustment for physician practice characteristics including percent African American or Medicaid patients. Disparities disfavoring African Americans in cholesterol testing and smoking cessation observed during 1985 to 1992 were not observed in 1995 to 2001. CONCLUSIONS: The findings suggest that race is associated with the type of primary care received by patients, at least for selected procedures, with evidence that some disparities have diminished over time.